2014
DOI: 10.1245/s10434-014-4018-6
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer and Synchronous Hepatic Metastases: Is It Possible to Recognize Candidates to R0 Resection?

Abstract: Our data suggest some clinical criteria that may facilitate selection of candidates to curative surgery, which offers the best survival chances, especially when associated with adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 28 publications
4
59
0
Order By: Relevance
“…Those results were maintained after propensity matching for the differences between groups. Other publications from the Far East [4][5][6][7], and some Western centers [14][15][16][17], have also suggested the safety of hepatectomy for gastric cancer liver metastases in selected patients. The results of this study also parallel the outcomes of hepatectomy for colorectal cancer liver metastases, where surgical resection is more common and is considered the standard of care for isolated hepatic metastases [11].…”
Section: Discussionmentioning
confidence: 99%
“…Those results were maintained after propensity matching for the differences between groups. Other publications from the Far East [4][5][6][7], and some Western centers [14][15][16][17], have also suggested the safety of hepatectomy for gastric cancer liver metastases in selected patients. The results of this study also parallel the outcomes of hepatectomy for colorectal cancer liver metastases, where surgical resection is more common and is considered the standard of care for isolated hepatic metastases [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recent results of the REGATTA trial, conducted in Asian patients, did not show any survival benefit of gastrectomy followed by chemotherapy compared with chemotherapy alone in advanced GC with a single noncurable factor, with an overall 2-year survival of 31.7 % for patients treated with chemotherapy alone versus 25.1 % for those treated with gastrectomy plus chemotherapy [33]. Palliative gastrectomy associated with liver resection and chemotherapy, when R0 resection can be obtained in patients able to endure difficult surgery, has been reported to improve overall survival in selected groups of patients [34].…”
Section: Palliationmentioning
confidence: 99%
“…We reviewed the 7 largest studies reported from 2012 to 2017, each with ≥ 50 patients who underwent hepatectomy for liver metastases from gastric cancer [12][13][14][15][16][17] [ Table 1]. In these series, the 3-and 5-year OS rates were 14.0% to 51.4% and 9.3% to 42.3%, respectively, with a median survival time (MST) of 13.0 to 40.8 months [12][13][14][15][16][17][18] . Solitary metastasis or a small number of metastatic nodules was highlighted as a favorable prognosis in most of the studies.…”
Section: Liver Metastasesmentioning
confidence: 99%